When are Firms Sued for Qualitative Disclosures? Implications of the Safe Harbor for Forward-Looking Statements - Cazier, Richard A.; Merkley, Kenneth J.; Treu, John S. (The Accounting Review, 2020)
ABSTRACT Prior research finds that positive tone in firms' qualitative disclosures increases the risk of shareholder lawsuits. However, federal securities laws provide a safe harbor intended to shield firms' forward-looking statements from legal liability. One implication of this safe harbor is that litigation risk potentially varies between qualitative forward- and non-forward-looking statements. Consistent with this implication, we find that positive tone in forward-looking qualitative statements is significantly less related to the likelihood of subsequent litigation than is positive tone in non-forward-looking qualitative statements. On average, we fail to find a significant association between qualitative forward-looking statements and subsequent litigation. We do find evidence, however, that positive tone in qualitative forward-looking statements relates positively to subsequent litigation in two U.S. circuits in which court rulings reduced safe harbor protections for forward-looking statements. Overall, our results are consistent with the safe harbor effectively shielding firms' qualitative forward-looking statements from litigation risk.